2008
DOI: 10.1155/2008/482373
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Evaluation of the Efficiency of TiO2/Zinc Phthalocyanine Nanocomposites as Photocatalysts for Wastewater Treatment Using Solar Irradiation

Abstract: This work reports the characterization of composites prepared by the association between zinc phthalocyanine (ZnPc) and titanium dioxide. These composites are better photocatalysts for wastewater decontamination mediated by solar radiation than pureTiO2, performance that remains even when reused. The UV-Vis diffuse reflectance absorption spectra show for these composites two intense absorption bands. The first covers the ultraviolet and part of the visible spectrum region until 460 nm (2.7 eV), whereas the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
1
53

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(132 citation statements)
references
References 63 publications
4
74
1
53
Order By: Relevance
“…Isso resulta em importantes alterações na fotofísica desses compostos, os quais podem se comportar como transportadores de cargas, como sugerido por Hoffmann, 36 ou ao levantamento da degenerescência, aumentando o desdobramento da banda em decorrência de distorções moleculares. [37][38][39] Em estudo recente, Machado e colaboradores, 40 reportaram que o espectro de absorção de agregados de ftalocianina de zinco suportados em partículas nanométricas de óxido de titânio apresenta uma perda marcante na estrutura da banda Q decorrente das fortes interações intermoleculares entre moléculas de ftalocianina de zinco no éxciton formado. Ademais, com base nas características espectrais observadas, concluíram que esses éxcitons se comportam como agregados tipo J de Frenkel.…”
Section: Figura 2 Esquema Das Reações De Obtenção Da Feofitina a Parunclassified
See 3 more Smart Citations
“…Isso resulta em importantes alterações na fotofísica desses compostos, os quais podem se comportar como transportadores de cargas, como sugerido por Hoffmann, 36 ou ao levantamento da degenerescência, aumentando o desdobramento da banda em decorrência de distorções moleculares. [37][38][39] Em estudo recente, Machado e colaboradores, 40 reportaram que o espectro de absorção de agregados de ftalocianina de zinco suportados em partículas nanométricas de óxido de titânio apresenta uma perda marcante na estrutura da banda Q decorrente das fortes interações intermoleculares entre moléculas de ftalocianina de zinco no éxciton formado. Ademais, com base nas características espectrais observadas, concluíram que esses éxcitons se comportam como agregados tipo J de Frenkel.…”
Section: Figura 2 Esquema Das Reações De Obtenção Da Feofitina a Parunclassified
“…Ademais, com base nas características espectrais observadas, concluíram que esses éxcitons se comportam como agregados tipo J de Frenkel. [36][37][38][39][40] As Figuras 4 e 5 apresentam a emissão de fluorescência da Chl em misturas etanol/água. A intensidade de fluorescência apresenta redução gradual no intervalo de 0 a 40% de água, e mais rapidamente entre 40 e 50%.…”
Section: Figura 2 Esquema Das Reações De Obtenção Da Feofitina a Parunclassified
See 2 more Smart Citations
“…Phthalocyanines can be one of the most efficient and stable class of photosensitizers for TiO 2 photocatalysts operating under visible light irradiation, as some studies have already reported [20][21][22][23][24][25][26][27][28][29], but the anchoring groups that could bind them on the nanoparticles surface [30] decisively determine the overall efficiency. Studies related to the stability of several coupling functionalities, such as carboxyl, phosphate, sulfonate, acetyl, silyl, hydroxyl, or amino reveal that carboxyl groups exhibit a very good stability during photocatalytic processes [31].…”
Section: Introductionmentioning
confidence: 99%